2020
DOI: 10.31083/j.rcm.2020.01.24
|View full text |Cite
|
Sign up to set email alerts
|

Management of heart failure in patients with end-stage kidney disease on maintenance dialysis: a practical guide

Abstract: End-stage kidney disease (ESKD) and heart failure (HF) often coexist and must be managed simultaneously. Multidisciplinary collaboration between nephrology and cardiology is critical when treating patients with such complicated physiology. There is no "one-size-fits-all" approach to the evaluation of patients with new left ventricular systolic dysfunction, and diagnostic testing should be adapted to an individual's risk factors. Guideline-directed medical therapy (GDMT) for systolic heart failure should be emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The mutual negative influence of impaired renal function and cardiovascular disease can lead to cardiorenal syndrome [ 40 , 41 , 42 ]. Morbid obesity and metabolic syndrome, which can lead to type 2 diabetes mellitus, are common satellites of cardiorenal syndrome in this situation [ 13 , 43 ].…”
Section: General Characteristics Of the Causes And Consequences Of Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutual negative influence of impaired renal function and cardiovascular disease can lead to cardiorenal syndrome [ 40 , 41 , 42 ]. Morbid obesity and metabolic syndrome, which can lead to type 2 diabetes mellitus, are common satellites of cardiorenal syndrome in this situation [ 13 , 43 ].…”
Section: General Characteristics Of the Causes And Consequences Of Esrdmentioning
confidence: 99%
“…In general, the development of renal fibrosis and ESRD depends on the degree of systemic and local homeostatic and proinflammatory changes in the kidneys, alongside dysfunctions from other organs, for example, in cardiorenal syndrome [ 40 , 41 , 42 ].…”
Section: Typical Low-intensity Inflammatory Processes In Ckd and Esrdmentioning
confidence: 99%
“…The semistructured interview from the perspective of doctor and patient was through the results of the previous interview, in the construction of the follow-up palliative care regimen, corresponding nursing care was given according to the reasons for the patients' not taking medicines on time, and a diet plan was formulated for the patients. It provided continuous nursing care for discharged patients through WeChat groups and WeChat official accounts and provided patients with professional, reliable, and stable information sources outside the hospital, so as to ensure the quality of patient' care outside the hospital and reduce the incidence of readmission [ 14 ]. The results of this study also found that there were no deaths in the two groups during the intervention period, which may be related to the short follow-up time in this study.…”
Section: Discussionmentioning
confidence: 99%
“…HD patients are at 12–36 times higher risk for the development of CHF [7, 8] . It has been reported that the prevalence of HF was as high as 33%–40% in Medicare ESKD patients in the USA [9, 10] . ESKD and HF have the same traditional common causes.…”
Section: Introductionmentioning
confidence: 99%